2020
DOI: 10.3390/ijms21239034
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Kinase 1 Pharmacological Inhibition Synergizes with DNA-Damaging Agents and Overcomes Platinum Resistance in Basal-Like Breast Cancer

Abstract: Basal-like breast cancer is an incurable disease with limited therapeutic options, mainly due to the frequent development of anti-cancer drug resistance. Therefore, identification of druggable targets to improve current therapies and overcome these resistances is a major goal. Targeting DNA repair mechanisms has reached the clinical setting and several strategies, like the inhibition of the CHK1 kinase, are currently in clinical development. Here, using a panel of basal-like cancer cell lines, we explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In this study, MCF 10A was applied as non-cancerous control for the MDA-MB-231 cells, which is a breast adenocarcinoma lineage. Cisplatin was shown to inhibit 50% of the growth of MDA-MB-231 at 6 µM 63 , which is a similar value to the ones we observed for MTT, NR or the phenothiazinium dyes. To reinforce the reproducibility of our results, we tested the LLC-MK2 cell lineage, which is widely used in cytotoxicity assays 65 , 66 , including phenothiazinium dyes 48 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, MCF 10A was applied as non-cancerous control for the MDA-MB-231 cells, which is a breast adenocarcinoma lineage. Cisplatin was shown to inhibit 50% of the growth of MDA-MB-231 at 6 µM 63 , which is a similar value to the ones we observed for MTT, NR or the phenothiazinium dyes. To reinforce the reproducibility of our results, we tested the LLC-MK2 cell lineage, which is widely used in cytotoxicity assays 65 , 66 , including phenothiazinium dyes 48 .…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have reported the use of cisplatin for in vitro assays in several cell lines 61,62 . Our results indicated three patterns of susceptibility to cisplatin, according to cell line: MCF 10A is a line applied as resistance control (for mammary cancer) to cisplatin, with IC 50 concentrations between 5 and 26 µM 63,64 . In this study, MCF 10A was applied as non-cancerous control for the MDA-MB-231 cells, which is a breast adenocarcinoma lineage.…”
Section: Discussionmentioning
confidence: 67%
“…Prexasertib has a good application value in ovarian neoplasms because there is evidence of cytotoxic T‐cell activation in the blood of patients when it is combined with PD‐L1 inhibitors 234 . Rabusertib showed a good synergistic activity in platinum‐resistant breast cancer cells 235 …”
Section: Kinase Groupsmentioning
confidence: 99%
“…Therefore, the combination of an ATM inhibitor and PARPi led to extensive DNA damage, activating the G2 damage checkpoint kinase cascade, allowing entry into mitosis, and resulting in mitotic and post-mitotic cell death [81]. The inhibition of CHK1 kinase, which is a key component of checkpoint mediate cell cycle arrest, also demonstrated synergy with olaparib in basallike breast cancer cells [82]. A phase I clinical trial further investigated the combination of CHK1 and olaparib and demonstrated preliminary antitumor activity in the context of BRCA MUT patients with high-grade serous ovarian cancer with a previous progression on PARPi alone [83].…”
Section: Parpi In Combination With Targeted Therapiesmentioning
confidence: 99%